EFEITO DE PREFERÊNCIAS COMO ENTRADAS PREPARADAS COM SACCHAROMYCES BOULARDII EM PÃO DE TRIGO - Alex Danny Chambi-Rodríguez (My University, 2023)
.
Keywords: Saccharomyces boulardii; Biology; Horticulture; Genetics; Bacteria; Probiotic; Saccharomyces boulardii; Biology; Horticulture; Genetics; Bacteria; Life Sciences Agricultural and Biological Sciences Forestry Agricultural and Food Sciences; Health Sciences Nursing Nutrition and Dietetics Food Science and Nutritional Studies